Subjective well-being and the duration of aggregate unemployment in Europe - Carsten Ochsen (Universität Rostock, Institut für Volkswirtschaftslehre, 2008)
This study examines whether the distribution of aggregate unemployment by duration affects individual well-being. Two hypotheses are provided to explain how the shares of short-term (up to 3 months) and long-term (more than 1 year) unemployed people could affect the well-being of the employed and unemployed: The severity hypothesis and the flow hypothesis. Using data from almost 300,000 individuals from 11 EU countries, an ordered probit estimator is used to analyze the impact of the distribution of aggregate unemployment by duration on individual well-being. We find significant evidence in favor of both the severity and the flow hypotheses. Hence, the fear of losing (or not finding) a job is more detrimental when the prospect is to remain unemployed for a longer time. At some point, however, both the employed and unemployed adapt to unemployment at the macro level. Using an alternative specification that allows for a duration-specific risk of becoming/being unemployed, we arrive at similar conclusions. What seems to bother people is thus not just the risk of becoming/remaining unemployed, but more so the risk of being out of work for 4 to 12 months.
Keywords: J64; I31; 330; unemployment; unemployment duration; life satisfaction; happiness; Zufriedenheit; Arbeitslosigkeit; Dauer; Arbeitsmarkt; Vergleich; EU-Staaten